Encompassing the Earth: Magellan's voyage from its political context to its expansion of knowledge. (November 2022) - Salonia, Matteo
Between 1519 and 1522, the Magellan–Elcano expedition completed the first circumnavigation of the world. This contribution offers a new interpretation of the political context leading to the voyage and, in particular, it considers the long history of Portuguese–Castilian rivalry in the Atlantic, reassessing the importance of the Treaty of Alcáçovas (1479). The second part of the article clarifies the objectives and achievements of the voyage, arguing that a reading of primary documents concerning Magellan's reward is necessary in order to understand the rationale behind the northerly route followed across the Pacific. It also sheds light on the momentous changes brought to Europe's geographical and cosmographical frameworks by the realization that all the oceans are one and the shattering of previous limits to human mobility. Finally, the article considers the images of Asian maritime and human geographies produced by one of the few survivors of the voyage, Antonio Pigafetta, in his Relazione, proposing a reading of this text centred around the concept of genuine curiosity, even in a broader context of Iberian empire-building.